Cinnamic Acid Increased the Incidence of Fusarium Wilt by Increasing the Pathogenicity of Fusarium oxysporum and Reducing the Physiological and Biochemical Resistance of Faba Bean, Which Was Alleviated by Intercropping With Wheat - Guo, Yuting; Lv, J.; Zhao, Q.; Dong, Yan; Dong, K. (Frontiers in Plant Science, 2020)
To explore the role cinnamic acid stress in faba bean physiology and disease resistance, and the potential mitigating effects of intercropping faba bean with wheat. Faba bean seedlings were grown with/out wheat in field and hydroponic conditions in the presence of different cinnamic acid concentrations and Fusarium oxysporum (FOF), and the occurrence of Fusarium wilt, oxidative stress, plant growth indices, and anti-pathogen defense system were analyzed. Cinnamic acid significantly increased the pathogenicity of FOF, reduced faba bean seedling growth, decreased peroxidase (POD), catalase (CAT), β-1,3-glucanase and chitinase activities, and increased the content of malondialdehyde (MDA) in a dose-dependent manner. Intercropping with wheat alleviated the effect of cinnamic acid stress, which promoted crop growth and decreased the incidence and disease index of Fusarium wilt. Thus, intercropping can effectively reduce the autotoxic effect of cinnamic acid on faba bean.